Association between Traditional Chinese medicine and a lower risk of dementia in patients with major depression: A case-control study. (5th October 2021) - Lin, Shun-Ku; Wang, Pin-Hsuan; Huang, Ching-Hsuan; Kuo, Yu-Hsien; Lai, Jung-Nien; Cheng-Chung Wei, James
Abstract: Ethnopharmacological relevance: Major depression is an important risk factor for dementia. Traditional Chinese medicine (TCM) can alleviate the symptoms of major depression. However, it is unclear whether TCM decreases the risk of dementia in patients with major depression. Therefore, in this nationwide case-control study, we aimed to evaluate the association between TCM and the risk of dementia. Materials and methods: We included 31, 981 major depression patients with dementia from the National Dementia Database as the case group, and 4391 major depression patients without dementia from a one-million random sample database as the control group. We matched age (plus or minus two years), sex, and year of depression diagnosis based on a 1:4 ratio. Result: There were 11, 724 and 2931 patients in the case and control groups, respectively. Based on a conditional logistic regression analysis, the TCM groups exhibited significantly lower odds ratios with a 95% confidence interval of 0.83 (0.74–0.91). TCM treatment for more than 90 days, dispersing Qi, and activating blood circulation resulted in lower dementia risk with the following odds ratios and 95% confidence intervals: 0.60 (0.56–0.68), 0.87 (0.74–1.08), and 0.66 (0.49–0.81). Conclusion: The results suggest that TCM is associated with lower dementia risk in major depression patients. Graphical abstract: Image 1